2001
DOI: 10.1093/ajcn/74.6.737
|View full text |Cite
|
Sign up to set email alerts
|

De novo lipogenesis during controlled overfeeding with sucrose or glucose in lean and obese women

Abstract: De novo lipogenesis increases after overfeeding with glucose and sucrose to the same extent in lean and obese women but does not contribute greatly to total fat balance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
103
1
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(110 citation statements)
references
References 18 publications
2
103
1
4
Order By: Relevance
“…In normal weight and obese women overfed for 4 d with 50% glucose or fructose above their energy requirement, de novo lipogenesis was found to be identical under both conditions. There was also no significant difference in plasma glucose, triacylglycerol, or insulin concentrations [45]. In healthy young normal weight subjects, a 6-d overfeeding with 3.5 g/kg fat-free mass/d (corresponding roughly to 30% energy requirements) fructose or glucose increased both VLDL-triacylglycerol concentrations and intrahepatic fat, with large interindividual variations, however [46].…”
Section: Are the Effects Of Fructose Different From Those Of Glucose?mentioning
confidence: 79%
“…In normal weight and obese women overfed for 4 d with 50% glucose or fructose above their energy requirement, de novo lipogenesis was found to be identical under both conditions. There was also no significant difference in plasma glucose, triacylglycerol, or insulin concentrations [45]. In healthy young normal weight subjects, a 6-d overfeeding with 3.5 g/kg fat-free mass/d (corresponding roughly to 30% energy requirements) fructose or glucose increased both VLDL-triacylglycerol concentrations and intrahepatic fat, with large interindividual variations, however [46].…”
Section: Are the Effects Of Fructose Different From Those Of Glucose?mentioning
confidence: 79%
“…The absolute value of DNL in this study can be judged as low. Technical factors are unlikely to explain the low rates of DNL reported by McDevitt et al, 20 since their method may overestimate DNL because the deuterium method, if anything, will result in an artifactual overestimation of a few percent of DNL, and elongation of fatty acids might add a further slight overestimation of DNL.…”
Section: Do Obese Women Convert More Cho To Fat Than Lean Women?mentioning
confidence: 85%
“…20 For example, it can be assumed that food (or meals) with low glycemic index may be more favorable in moderating DNL since the pattern of CHO oxidation and storage will be delayed as compared to food with high glycemic index. 21 As a result, a large positive excursion is prevented in respiratory quotient in the postprandial phase, a time at which DNL is stimulated.…”
Section: Fat Balance and De Novo Lipogenesis Y Schutzmentioning
confidence: 99%
“…The extent to which excessive fructose, aspartame and caramel consumption might contribute to the high prevalence of liver disease in western societies and to the progression of NAFLD to NASH has not been investigated. One study of lean women found that four days of overfeeding with sucrose (glucose plus fructose) drink increased de novo lipogenesis by 200% to 300% (21). Another feeding study showed that two days of a high-fructose diet (30% of the total energy consumed per day, consumed as a sweetened beverage at every meal) resulted in decreased postprandial glucose concentration and insulin response, and prolonged alimentary lipemia in women (22).…”
Section: Discussionmentioning
confidence: 99%